A new species within the Eurytemora affinis complex (Copepoda: Calanoida) from the Atlantic Coast of USA, with observations on eight morphologically different European populations - Alekseev, Victor R.; Souissi, Anissa (Zootaxa, 2011)
Eurytemora carolleeae sp. nov. (Crustacea: Copepoda: Calaniformes) is described from the Chesapeake Bay, USA. The new species belongs to the Atlantic clade of the Eurytemora affinis complex outlined by previously published molecular work but poorly characterized morphologically. To discriminate E. carolleeae we compare specimens from the Atlantic USA clade with specimens from the type population of E. affinis (Poppe, 1880) from the Elbe River Estuary (Germany), as well as with eight other European coastal populations. Several important morphological characters clearly separate the North American E. cf. affinis from the European clade that include both sexes: a large outside orientated dent on the mandible, and clearly observable seta segmentation in the caudal rami and swimming legs. Unlike E. affinis, the newly described species possesses wing-like outgrowths on the genital double-somite and a very small spine near the distal seta insertion point in P5 in females. In males, the specific characters include naked dorsal and ventral sides of the caudal rami, and a cylindrical shape of exopod on the left P5, in contrast to a triangular shape of the segment in E. affinis. The new species was also found in Canada (St. Lawrence Estuary) and as an invasive species in the Baltic Sea. Eurytemora carolleeae is possibly widely distributed along the North American Atlantic coast, as well as in inland waters from Great Lakes to Mexico.